Fertility after photodynamic inactivation of bacteria in extended boar semen - Luther, Anne-Marie; Varzandeh, Mohammad; Beckermann, Christina; Feyer, Leon; Maaßen, Isabel Katharina; Oldenhof, Harriёtte; Hackbarth, Steffen; Waberski, Dagmar (Frontiers in Microbiology, 2024)
Antimicrobial resistance is an increasing challenge in semen preservation of breeding animals, especially in the porcine species. Bacteria are a natural component of semen, and their growth should be inhibited to protect sperm fertilizing capacity and the female’s health. In pig breeding, where semen is routinely stored at 17°C in the liquid state, alternatives to conventional antibiotics are urgently needed. Photodynamic inactivation (PDI) of bacteria is a well-established tool in medicine and the food industry but this technology has not been widely adopted in semen preservation. The specific challenge in this setting is to selectively inactivate bacteria while maintaining sperm integrity and functionality. The aim of this study was to test the principle of PDI in liquid stored boar semen using the photosensitizer 5,10,15,20-tetrakis(N-methyl-4-pyridyl)-21H,23H-porphine (TMPyP) and a white light LED-setup. In the first step, photophysical experiments comprising singlet oxygen phosphorescence kinetics of TMPyP and determination of the photosensitizer triplet time revealed a sufficiently high production of reactive singlet oxygen in the Androstar Premium semen extender, whereas seminal plasma acted as strong quencher. In vitro experiments with extended boar semen showed that the established PDI protocol preserves sperm motility, membrane integrity, DNA integrity, and mitochondrial activity while efficiently reducing the bacteria below the detection limit. A proof-of-concept insemination study confirmed the in vivo fertility of semen after photodynamic treatment. In conclusion, using the PDI approach, an innovative tool was established that efficiently controls bacteria growth in extended boar and maintains sperm fertility. This could be a promising contribution to the One Health concept with the potential to reduce antimicrobial resistance in animal husbandry.